Doubt a parable - Shanley, John Patrick 1950- (Theatre Communications Group, 2005)
Set in a Bronx Catholic school in 1964, a nun is faced with uncertainty as she has grave concerns for a male colleague.
Keywords: Klerus; Catholics -- Drama; Child sexual abuse -- Drama; Clergy -- Drama; Nuns -- Drama